2015
DOI: 10.1063/1.4905562
|View full text |Cite
|
Sign up to set email alerts
|

Experimental triplet and quadruplet fluctuation densities and spatial distribution function integrals for pure liquids

Abstract: Fluctuation solution theory has provided an alternative view of many liquid mixture properties in terms of particle number fluctuations. The particle number fluctuations can also be related to integrals of the corresponding two body distribution functions between molecular pairs in order to provide a more physical picture of solution behavior and molecule affinities. Here, we extend this type of approach to provide expressions for higher order triplet and quadruplet fluctuations, and thereby integrals over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(61 citation statements)
references
References 60 publications
(126 reference statements)
0
61
0
Order By: Relevance
“…Indeed, previous studies have shown that the GCE distributions are not Gaussian (or symmetric) and therefore this assumption is not justified for the present purposes. 14,20 This point will also be discussed further in Sec. III.…”
Section: Ds/rmentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, previous studies have shown that the GCE distributions are not Gaussian (or symmetric) and therefore this assumption is not justified for the present purposes. 14,20 This point will also be discussed further in Sec. III.…”
Section: Ds/rmentioning
confidence: 97%
“…4,11,12 Nevertheless, there is interest in the properties of the resulting non-Gaussian distributions. 4,[12][13][14] The third and higher moments of these distributions are finite and have been developed by Greene and Callen. 15 They are important for understanding higher thermodynamic derivatives, especially close to the critical point, which characterize the behavior of fluids and their mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations